EFEKTIVITAS SISTEM ADMINISTRASI MELALUI SISTEM INFORMASI MANAJEMEN KEPEGAWAIAN (SIMPEG): STUDI DI BADAN KEPEGAWAIAN PENDIDIKAN DAN PELATIHAN DAERAH KABUPATEN KAPUAS (Journal Ilmu Sosial, Politik dan Pemerintahan, 2016)
This study aims to describe and analyze the effectiveness of the administration system through a Management Information System (SIMPEG) in Education and Training Board of Civil Service Agency, Kapuas regency in Civil Service Administration Division. The focus of this research study is to determine the effectiveness of the administration system using indicator of the effectiveness of Richard M. Steers which is the optimization objectives, systematic perspective and behavior of employees in the organization as well as in the use of Management Information System which are the input, process and output.